Communicating to prospective students through appropriate sources of information - Melanie Wiese; Yolanda Jordaan; Cornelius van Heerden (Communicare)
A proper assessment of the usefulness of the sources of information considered by prospective students could enable higher education institutions (HEIs) to allocate funds, time and resources more efficiently and effectively. The main objective of this study was to determine students’ perceptions on the usefulness of sources of information that they used to select a public HEI in South Africa, and further to establish whether differences occur between the perceptions of students from various institutions. A quantitative study with a self-administrated questionnaire was used to obtain information by means of a non-probability convenience sample of 1 241 students from six public HEIs in South Africa. The findings indicated that prospective students find sources of information coming directly from a public HEIs - such as campus visits and open days, university publications and websites – to be of most use, while information from mass media, such as radio, television, magazines and newspaper advertisements are less important. The responses of students from the different institutions varied significantly regarding the usefulness of sources of information in selecting a public HEI. Although university publications, campus visits and open days, and also websites ranked high, the importance ranking between respondents from different institutions varied. The findings can be used to develop student-focused marketing communication that could aid prospective students in making more informed decisions about the public higher education institution they wish to attend.